Characterization of the acclimation period before anaerobic dehalogenation of halobenzoates. - Linkfield, T G (1989)
The acclimation periods prior to detectable dehalogenation of halogenated benzoates in anaerobic lake sediments ranged from 3 weeks to 6 months. These acclimation periods were reproducible over time and among sampling sites and were characteristic of the chemical tested. The lengthy acclimation period appears to represent an induction phase in which little or no aryl dehalogenation is observed, followed by an exponential increase in activity typical of an enrichment response. Continuous growth from the time of the first exposure to the chemical is inconsistent with the extremely low per-cell activities estimated for the early days of the acclimation period and the fact that the dehalogenation yields no carbon to support microbial growth. The finding of a characteristic acclimation time for each chemical argues against nutritional deficiency, inhibition, or predation as an explanation for this phase of metabolism, while the reproducibility of the findings with time and space and among replicates argues against genetic changes as the explanation. The acclimation times did correlate with the eventual dehalogenation rates. This may reflect the general energy limitations in the anaerobic communities and suggests that those chemicals with faster dehalogenation rates provide more energy for the induction and growth phases of the active population.